Nonlinear rheology of glass-forming colloidal dispersions: transient stress–strain relations from anisotropic mode coupling theory and thermosensitive microgels. (20th May 2015) - Amann, C M; Siebenbürger, M; Ballauff, M; Fuchs, M
Abstract Transient stress–strain relations close to the colloidal glass transition are obtained within the integration through transients framework generalizing mode coupling theory to flow driven systems. Results from large-scale numerical calculations are quantitatively compared to experiments on thermosensitive microgels, which reveals that theory captures the magnitudes of stresses semi-quantitatively even in the nonlinear regime, but overestimates the characteristic strain where plastic events set in. The former conclusion can also be drawn from flow curves, while the latter conclusion is supported by a comparison to single particle motion measured by confocal microscopy. The qualitative picture, as previously obtained from simplifications of the theory in schematic models, is recovered by the quantitative solutions of the theory for Brownian hard spheres.